2023
DOI: 10.3390/nano13121894
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Optical Anisotropy of Spider Scales and Silk: The Use of Chromaticity and Azimuth Colors to Optically Characterize Complex Biological Structures

Abstract: Herein, we give an overview of several less explored structural and optical characterization techniques useful for biomaterials. New insights into the structure of natural fibers such as spider silk can be gained with minimal sample preparation. Electromagnetic radiation (EMR) over a broad range of wavelengths (from X-ray to THz) provides information of the structure of the material at correspondingly different length scales (nm-to-mm). When the sample features, such as the alignment of certain fibers, cannot … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Another conventional method to solve this issue of fast versus slow axis is to use a color-shifting plate (usually a 530 nm wavelplate) in cross-polarized imaging, which determines positive and negative contributions to the refractive index with blue-red perpendicular directions corresponding to the n e (slow)-n o (fast) orientations of silk. [28] Finally, with 𝛿, 𝜃 determined via fit or from analytical expression using single a image from a 4-pol. camera, all four Stokes parameters can be defined: S 0 (intensity) and S 1,2,3 .…”
Section: All Four Stokes Parameters From 4-pol Imagingmentioning
confidence: 99%
“…Another conventional method to solve this issue of fast versus slow axis is to use a color-shifting plate (usually a 530 nm wavelplate) in cross-polarized imaging, which determines positive and negative contributions to the refractive index with blue-red perpendicular directions corresponding to the n e (slow)-n o (fast) orientations of silk. [28] Finally, with 𝛿, 𝜃 determined via fit or from analytical expression using single a image from a 4-pol. camera, all four Stokes parameters can be defined: S 0 (intensity) and S 1,2,3 .…”
Section: All Four Stokes Parameters From 4-pol Imagingmentioning
confidence: 99%
“…In the case of absorption-dominated transmission changes, it is shown that a cos-fit can be used for each pixel of the camera and obtained using only three points (three from four polarisation images). This technique is demonstrated for transmission and reflection modes using natural olivine micro-crystals, but it is fully transferable to other polarisationresolved imaging techniques; e.g., bio-medical techniques [14,15], 3D optical coherent tomography [16,17], analysis of structural colours in natural materials [18], and industrial applications, such as edge detection of fast moving materials and workpieces [19].…”
Section: Introductionmentioning
confidence: 99%